(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The given article provides an overview of phrases related to the concept of gender used in the process of learning English. It discusses their origins and characteristics, as well as brief information about research conducted by scholars, supplemented with explanations.